"When I say I'm depressed, it's like anger." An exploration of the emotional landscape of climate change concern in Norway and its psychological, social and political implications. (February 2023) - Marczak, Michalina; Winkowska, Małgorzata; Chaton-Østlie, Katia; Morote Rios, Roxanna; Klöckner, Christian A.
Abstract: Climate anxiety discourse focuses predominantly on individualised and potentially mentally disturbing aspects of emotional responses to the awareness of climate change which can silence the mobilising charge of strong emotions in response to climate change. We critically examine this perspective and explore the range, context, and perceived effects of emotional responses to climate change based on 33 in-depth interviews with people self-identified as highly concerned about this issue in the context of oil-wealthy Norway. Thematic analysis revealed that lived emotional experience of concern about climate change is characterised by a complex palette of co-occurring and dynamically linked emotions reported in relation to 16 evocative themes. We analyse the perceived effects of these emotions focusing on five areas: participants' mood and wellbeing, concerns about existing and hypothetical children, feelings of alienation, responsibility for the climate situation, and positive experience in the context of climate change. We discuss the psychological, social and political implications of participants' emotional experience, considering the Norwegian context, and we conclude that it goes beyond potentially debilitating and paralysing feelings, and includes politically charged moral anger and collective guilt, as well as love for nature, and a sense of community around collective climate action. Highlights: We critically reflect on the notion of "climate anxiety" We conduct in-depth interviews with highly concerned people in the privileged context of oil-wealthy Norway Participants reported experiencing a complex palette of emotions in relation to 16 evocative themes Beyond fear and grief, participants reported also, e.g., moral anger, collective guilt and excitement around collective action. We move away from pathologisation of emotional responses to climate change and discuss their mobilising charge.